2015
DOI: 10.1007/s00240-015-0823-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the mineral composition of ureteral stone using non-contrast computed tomography

Abstract: We investigated the correlation between computed tomography (CT) density of ureteral stones and their mineral composition. A total of 346 patients who underwent ureteroscopic lithotripsy for calculi all fragments of which were acquired at a single institution from 2009 to 2011 were analyzed. The maximum and mean CT densities were measured preoperatively. A mineral analysis revealed calcium oxalate in 203 (58.7 %), mixed calcium oxalate and calcium phosphate in 78 (23.0 %), calcium phosphate in 18 (5.2 %), uric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…This is because HUs predict the stone hardness and fragility. In our previous study, we also proved that HUs could predict stone composition through a multivariate analysis [ 28 ]. Considering clinical use, it is easy to measure HUs using NCCT; however, it is usually difficult to predict the stone composition preoperatively.…”
Section: Discussionmentioning
confidence: 81%
“…This is because HUs predict the stone hardness and fragility. In our previous study, we also proved that HUs could predict stone composition through a multivariate analysis [ 28 ]. Considering clinical use, it is easy to measure HUs using NCCT; however, it is usually difficult to predict the stone composition preoperatively.…”
Section: Discussionmentioning
confidence: 81%
“…In a study by Deveci et al, pure uric acid stones were shown to be mean 311 HU (range, 112-436 HU) and mixed uric acid stones were mean 331 HU (range, 110-427 HU) [7]. In another study, the mean density of uric acid stones was reported as mean 541.5 ± 161.1 HU [11]. Although there is no standard value for standard density of uric acid stones on non-contrast CT, in the light of the previous research it seems to be <700 HU.…”
Section: Medical Dissolution Therapy For Kidney Stone With Low Densitmentioning
confidence: 95%
“…The mean of the 3 measurements was accepted as the absolute CT value for a particular stone ( Figure 3). The densities of the uric acid stones were found to be 311 HU (range 112-436 HU), 587 ± 329 HU, and 541.5 ± 161.1 HU in three different studies [7,10,11]. Stones with density <800 HU were accepted as low density stones with a uric acid component and treatment was planned accordingly.…”
Section: Ct Protocolmentioning
confidence: 99%
“…With CT imaging, Hounsfield unit density can be used to characterize differences in radiodensities among urinary stones and can be helpful in planning alternative treatment for patients with a likelihood of a poor outcome from shock wave lithotripsy [39][40][41][42]. Dual-energy CT is able to differentiate uric acid, cystine, struvite and mixed stones from other types of stones [43,44].…”
Section: Key Pointsmentioning
confidence: 99%